2018
DOI: 10.1111/apt.15006
|View full text |Cite
|
Sign up to set email alerts
|

Serum M2BPGi level and risk of hepatocellular carcinoma after oral anti‐viral therapy in patients with chronic hepatitis B

Abstract: Summary Background Mac‐2 binding protein glycosylation isomer (M2BPGi) is an emerging biomarker for risk prediction of liver disease, but data remain sparse for patients with chronic hepatitis B (CHB) who are treated with nucleos(t)ide analogues (NA). Aim To clarify serial changes in M2BPGi and its association with subsequent hepatocellular carcinoma (HCC) development in NA‐treated CHB patients. Methods We enrolled 384 previously untreated CHB patients who received NAs. Among them, 195 had baseline cirrhosis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…First, it is increasingly apparent that M2BPGi is not solely a marker of liver fibrosis. M2BPGi levels are elevated in the setting of nonspecific acute liver injury, and M2BPGi levels decline quickly with antiviral treatment for HBV and HCV, too quickly to be due to regression of fibrosis . Bekki et al demonstrated that hepatic stellate cells produce M2BPGi in vitro and that M2BPGi signaling between hepatic stellate cells and Kupffer cells may promote a fibrogenic program.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is increasingly apparent that M2BPGi is not solely a marker of liver fibrosis. M2BPGi levels are elevated in the setting of nonspecific acute liver injury, and M2BPGi levels decline quickly with antiviral treatment for HBV and HCV, too quickly to be due to regression of fibrosis . Bekki et al demonstrated that hepatic stellate cells produce M2BPGi in vitro and that M2BPGi signaling between hepatic stellate cells and Kupffer cells may promote a fibrogenic program.…”
Section: Discussionmentioning
confidence: 99%
“…For example, macrophage‐specific activation marker sCD163 was proved to predict significant portal hypertension accurately combined with ELF results . Biomarker such as serum Mac‐2‐binding protein glycosylation isomer (M2BPGi) could predict HCC in nucleos(t)ide analogues‐treated CHB patients . The probability of combing those markers with LSM to predict HCC in CHB patients need to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with undetectable HBV DNA during NA therapy, a higher pre-treatment M2BPGi level is associated with an increased risk of HCC development [86,88]. Cheung et al compared 57 NA-treated patients, with undetectable HBV DNA and HCC development, with 57 controls.…”
Section: M2bpgi and Its Characteristicsmentioning
confidence: 99%
“…Moreover, in patients with cirrhosis, the baseline M2BPGi level was associated with HCC occurrence, while the M2BPGi levels at year 1 or 2 were not independently predictive. As a result, a risk score for HCC occurrence was developed using the baseline M2BPGi, age, and body mass index at 3, 5, and 10 years, respectively [86]. Shinkai et al also reported that serum M2BPGi levels ≥1.215 C.O.I.…”
Section: M2bpgi For Hcc Prediction In Chbmentioning
confidence: 99%
See 1 more Smart Citation